An enquiry into the financial feasibility of Janata Bank Limited, Mohammadpur corporate branch - Rahman, Erham Ebne Abdur (BRAC University, 2016)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2016.